Fungsi Dewan Perwakilan Rakyat Daerah dalam Penanganan Pandemi Corona Virus Disease 2019: (Studi Undang-Undang Nomor 6 Tahun 2018 tentang Kekarantinaan Kesehatan) - Melta Setya Rahayu Pujianti (CV Rewang Rencang, 2020)
The State of Indonesia is a country that is in the area of intersection between disasters, intercontinental, intercultural, between economic forces, even between civilities that result in the emergence of potential disasters and extraordinary events or known as Emergencies (State Emergency). Therefore, the device of legislation in normal circumstances is not compatible when applied under abnormal circumstances because generally abnormal circumstances are unpredictable. In Indonesia, the constitutional basis for implementing the Emergency Law is stipulated in Article 12 of the 1945 Constitution. Unfortunately, Article 12 of the 1945 Constitution is only once referred to in the laws and regulations labeled